Do pre-service teachers feel ready to teach with digital technologies? A study in two teacher training institutions in Costa Rica (Research, Society and Development, 2021)
This study aims to identify both the level and frequency of digital technology use and perceived self-efficacy levels of pre-service teachers (n = 341). We collected data in Costa Rica through a survey during the 2016–2017 academic year; the survey includes closed-ended items on the use and frequency of digital technologies along with open-ended questions. Findings suggest that a majority of pre-service teachers frequently use digital technologies for both professional and private use and specifically the mobile phone and social media. Results further suggest they find themselves self-efficacious in the use of “traditional” digital technologies that are also used in teacher training by professors/teacher trainers such as laptop, email and video. They are less confident in using mobile phones and social media for teaching even though they use them extensively for their professional development.